New perspectives on international party assistance. Issue 6 (18th August 2022) - Storm, Lise
ABSTRACT: With its micro-level perspective, this article addresses a gap in the literature on democracy support. The study focuses on the analysis of eight national international party assistance (IPA) providers and their penchant for tame, regime-compatible support, based on data gathered in more than fifty qualitative interviews with practitioners, experts, policymakers and government analysts over a 4-year period (2015–2018). Structured around the four factors that distinguish national IPA providers – objectives, organizational model, financial scale and modes of intervention – as well as provider age, the analysis centres on the role played by survival-seeking behaviour when providers opt for tame assistance, with a view to identify variation between the vulnerable and less vulnerable NGOs. The study finds that, while survival-seeking behaviour often plays a role, it is frequently not the main factor driving tame assistance, even amongst those providers whose survival is most at stake. Rather, drivers of tame assistance vary from case to case, habitually involving one or more of the following factors: institutional set-up, branding and growth. Thus, if the sector is to move away from tame assistance, we need to look beyond macro-level factors and also focus on ameliorating institutional constraints and the factors that shape agency at the micro-level.